Characteristics of 2 Different Commercially Available Implants with or without Nanotopography - Ali Alenezi; Yoshihito Naito; Martin Andersson; Bruno R. Chrcanovic; Ann Wennerberg; Ryo Jimbo (Hindawi Limited, 2013)
The aim of this study was to assess histologically and histomorphometrically the early bone forming properties after 3 weeks for 2 commercially available implants, one supposedly possessing nanotopography and one without, in a rabbit femur model. Twenty-four implants divided equally into 2 groups were utilized in this study. The first group (P-I MICRO+NANO) was a titanium oxide (TiO2) microblasted and noble gas ion bombarded surface while the second group (Ospol) was anodic oxidized surface with calcium and phosphate incorporation. The implants were placed in the rabbit femur unicortically and were allowed to heal for 3 weeks. After euthanasia, the samples were subjected to histologic sectioning and bone-implant contact and bone area were evaluated histomorphometrically under an optical microscope. The histomorphometric evaluation presented that the P-I MICRO+NANO implants demonstrated significantly higher new bone formation as compared to the Ospol implants. Within the limitations of this study, the results suggested that nanostructures presented significantly higher bone formation after 3 weeks in vivo, and the effect of chemistry was limited, which is indicative that nanotopography is effective at early healing periods.